Analisis Kebijakan Penyaluran Program Bantuan Sosial Kepada Masyarakat Akibat Pandemi Covid-19 di Kelurahan Panorama Kota Bengkulu - Yohanes Susanto; Romdana Yahya (Jurnal STIA Bengkulu, 2022)
This study aims to determine the Policy for Distribution of Social Assistance Programs to the Community Due to the Covid-19 Pandemic in the Panorama Village, Bengkulu City, the type of research carried out is descriptive qualitative research, where data collection techniques are obtained with primary and secondary data in the form of articles, journals, news, and other literature studies related to this research. Based on the results of research related to the policy of distributing social assistance programs to the community due to the Covid-19 pandemic in the Panorama Village, Bengkulu City through the role of the sub-district government in collaboration with their staff including RT, RW and youth organizations and public order has been running very well and on target.